Bridal mysticism, virtual marriage and masculinity in the Moravian hymnbook "Kleines Brüdergesangbuch" Journal for Religion, Film and Media - Benedikt Bauer (Journal for Religion, Film and Media, 2018)
This article discusses the connection of virtual interaction, masculinity and bridal mysticism in the Moravian hymnbook "Kleines Brüdergesangbuch" (1754). Hereto, the motifs inherent in the hymnbook are examined according to the anthropological presentations as well as the perception of the divine, i.e. Jesus Christ, using mainly the conceptions of virtual interaction (S. Knauß) and hegemonic masculinity (R. Connell).